How to measure anything : finding the value of "intangibles" in business - Hubbard, Douglas W., 1962- (Hoboken, N.J. : Wiley, 2010)
Now updated with new research and even more intuitive explanations, a demystifying explanation of how managers can inform themselves to make less risky, more profitable business decisions. This insightful and eloquent book will show you how to measure those things in your own business that, until now, you may have considered "immeasurable," including customer satisfaction, organizational flexibility, technology risk, and technology ROI.: Adds even more intuitive explanations of powerful measurement methods and shows how they can be applied to areas such as risk management and custome.
Intangibles and the challenge -- An intuitive measurement habit : Eratosthenes, Enrico, and Emily -- The illusion of intangibles : why immeasurables aren't -- Clarifying the measurement problem -- Calibrated estimates : how much do you know now? -- Measuring risk through modeling -- Measuring the value of information -- The transition : from what to measure to how to measure -- Sampling reality: how observing some things tells us about all things -- Bayes : adding to what you know now -- Preference and attitudes : the softer side of measurement -- The ultimate measurement instrument : human judges -- New measurement instruments for management -- A universal measurement methods : applied information economics.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Intangible property -- Valuation; BUSINESS & ECONOMICS -- Accounting -- Financial; Intangible property -- Valuation; x; Intangible assets; Asset valuation